The Effect of Metabolic Syndrome on the Outcome of Hepatitis B-Associated Hepatocellular Carcinoma Patients After Hepatectomy: A Multicenter Study - Dai, Junlong; Zhu, Xinrui; Shen, Junyi; Zhang, Yu; Xie, Fei; Yu, Yu; Jiang, Kangyi; Wen, Tianfu; Li, Chuan (Frontiers in oncology, 2022)
With changes in dietary patterns and modern lifestyles, the prevalence of metabolic syndrome (MetS) in hepatitis B virus (HBV)-associated hepatocellular carcinoma (HCC) patients is increasing. The purpose of our study is to explore the impact of MetS on the prognosis of HBV-associated HCC patients following radical hepatectomy. Data on consecutive HCC patients who underwent radical hepatectomy were prospectively obtained and retrospectively analyzed from seven medical centers in west areas of China. Propensity score matching (PSM) analysis was conducted to balance the heterogeneity between MetS-HBV-HCC group and HBV-HCC group. Surgical outcomes have been contrasted between the two groups. In 984 patients, 179 (18.19%) were diagnosed with MetS. Patients in the MetS-HBV-HCC group had higher CCI score (8.7 [0.0, 12.2] vs. 0.0 [0.0, 8.7], = 0.048) and a higher rate of severe complications (Clavien-Dindo ≥3, 7.82% vs. 4.10%, = 0.035), to be more precise: postoperative liver failure, hydrothorax, and hyperglycemia. Patients in the MetS-HBV-HCC group tended to have worse 5-year overall survival (OS) rate (61.45% vs. 69.94%, = 0.027) and recurrence-free survival (RFS) rate (62.57% vs. 53.66%, = 0.030), consistent with the results of the competing risk models. Last, MetS was identified to be an independent unfavorable prognostic factor in the multivariate analysis. The involvement of MetS increased the risk of postoperative complications and worsens the overall survival and recurrence-free survival time, reminding us to be more prudent to face metabolic disorder among tumor patients.